Carbonation Resistance of Reinforced Concrete under Bending Load - Yan Liu; Jun Ren; Qiuli Gao; Shengli Zhao (Fracture and Structural Integrity)
Fly ash has been used more and more often to take the place of cement as the admixture of concrete in the construction of concrete buildings. However, with the increase of the carbon dioxide (CO2) concentration in the atmosphere, carbonization damage has become an essential factor affecting the durability of fly ash concrete. Here a long-term bending load device was developed to explore how the pouring surface and the bending load affect the carbonization resistance of reinforced concrete under rapid carbonization. In addition, the relationship between the bending-tension and bending-compression loads with respect to the carbonization damage of test blocks was also investigated. Due to the differences in the concrete compactness, the carbonization depth of the pouring surface was found to be greater than that of the bottom at the same position. To a certain extent, with the increasing bending-load stress, different carbonization resistances were observed in the bending-tension zone and the bending-compression zone of the concrete test blocks. Meanwhile, to study the relationship between the carbonization damages in the bending-tension zone and the bending-compression zone of concrete test blocks, a carbonization influence coefficient of bending tension-compression load was proposed, which provides a convenient and scientific guidance for the detection and evaluation of concrete carbonization damages in practical engineering.